The Existence of Islamic Banks and Non-Bank Financial Institutions in Promoting Islamic Financial Inclusion - Muhammad Naufal Faqiih; Aghna Karnys Izza Muhammad; Sulthon Maulana Arsyih; Daffa Ryuki Prabowo; Muhammad Faiz Andreaz Fawwaz; Fadhli Suko Wiryanto (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study is motivated by the persistent gap between Islamic financial literacy and Islamic financial inclusion in Indonesia, despite the continuous growth of Islamic financial industry assets. The research aims to describe the existence of Islamic banks and Islamic non-bank financial institutions (NBFIs) in promoting Islamic financial inclusion in Indonesia. This study adopts a qualitative approach using a descriptive design and a library research method, relying on secondary data analyzed through content analysis techniques. The findings indicate that Islamic banks and Islamic NBFIs, including Islamic insurance, Islamic pension funds, Islamic pawnshops, and Islamic fintech, continue to experience asset growth and service diversification. However, this growth has not been fully translated into a corresponding increase in Islamic financial inclusion. The study also finds that Islamic financial literacy levels are significantly higher than inclusion levels, suggesting that increased public knowledge does not automatically lead to active utilization of Islamic financial services. Furthermore, structural issues such as regulatory inconsistency, limited product innovation, and unequal digital readiness across institutions remain key barriers. The study concludes that stronger synergy among regulators, Islamic financial institutions, academics, and society is required to enhance literacy, promote innovation, harmonize regulations, and optimize digital technology for sustainable Islamic financial inclusion.